You are on page 1of 21

# 8

LAGRANGE
8.1 Lagrange

q1 , q 2 , q3 .
Lagrange.
,
.
q1 , q 2 , q3
x, y, z q1 , q 2 , q3
, (7.1.1) (7.1.2).
r = r (q j , t) = xi + yj + zk ,
x = x(q j , t) , y = y(q j , t) , z = z(q j , t) , j = 1, 2 ,3

(8.1.1)

q j = q j (x, y, z, t) , j = 1, 2,3.

(8.1.2)

(8.1.1)

dx
x dq1 x dq 2 x dq 3 x
= x& =
+
+
+
dt
q1 dt q 2 dt
q 3 dt
t
x& =

x
x
x
x
q& 1 +
q& 2 +
q& 3 +
.
q1
q 2
q 3
t

x&
x
=
, j = 1, 2 ,3.
q& j q j

&
x

q j

d x

, j = 1, 2 ,3
dt q j

(8.1.1).

F = Fx i + Fy j + Fz k .
&& = Fx , my
&& = Fy , mz
&& = Fz .
mx

148

x y z
,
,
q j q j q j

q j

m &&
x

+ &&
y

y
q j

+ &&
z

z
x
y
z
+ Fy
+ Fz
=
= Fx
q j
q j
q j
q j

Qj ,

Q j .
&&
x

x
q j

= &&
x

&
x
&j
q

&
x
d x&
d x& d x&
d x d x&
&
&
&
&
&
&
.
x
x

=
x
x

=
x
x
q j
dt q& j
dt q& j dt q& j
dt q j dt q& j

&&
x

x
q j

d 1 2 1 2
&
&

x
x
dt q& j 2 q j 2

&&y

q j

m &&
x

y
+ &&

y
q j

z
+ &&

z
=
q j

y
z
&&z
.
q j
q j

d 1 2 1 2 1 2
1 2 1 2 1 2
& +
& +
y& + z& m
y& + z& =

x
x
dt q& j 2
2
2
2
2
q j 2

d T T
,

dt q& j q j

T =

1
m x& 2 +y& 2 +z& 2
2

) .
d T T

dt q& j q j

Q j , j = 1, 2 ,3.

(8.1.3)

(8.1.3) Lagrange
.
F .
Q j U

= U(q j ,t) ,

(7.4.11)

Qj =

U
, j = 1, 2 ,3 .
q j

Lagrange (8.1.3) :
d T T

dt q& j q j

U
q j

, j = 1, 2 ,3.

(8.1.4)

(8.2.4)
L = TU

(8.1.5)

149

L
T
,
=
q& j q& j

L (T U)
=
, j = 1, 2 ,3 .
q j
q j

Lagrange
U = U(q j ,t)
d L L

dt q& j q j

0 , j = 1, 2 ,3.

(8.1.6)

(8.1.5) Lagrange
, ,
L = L(q j , q& j , t),j = 1, 2,3 .

F = m/r 2 .

.
. (r, )
T=

1
m
m(r& 2 +r 2& 2 ) , U =
.
2
r

Lagrange
1
m
m(r& 2 +r 2 & 2 ) +
.
2
r

L=

q1 = r

q 2

= .

L
L
L
m L
= mr& ,
= mr 2& ,
= mr& 2 2 ,
= 0.
&
&
r
r

(8.1.6) ,
m(r&& r& 2 ) =

8.2

m
r

d 2&
(r ) = 0 .
dt

Lagrange

) Lagrange

N k . n = 3N k

r = r (q1 , q 2 ,...,q n , t) ,

= 1, 2,..., N .

(8.2.1)

r =

n r
r
r
r
q1 + q 2 + ... + q n = q j .
q1
q 2
q n
j=1 q j

(8.2.2)

150

m &&r = F

=1

W = (F

=1

n N

W = F

j=1 =1

q j

m &&
r ) r

r
q j =

=1

m &r& q

=1

0.

0.

,
r
,
q j

Qj

=1

m &r&

=1

r
qj

(Q j + j )q j = 0.

(8.2.3)

j=1

j D Alembert j
r
d N
m r&

dt =1
q j

j = m &&r r

=1

q j

, (8.2.1) dr = r dq j + r
q
t
n

j=1

m r&

d r

.
dt q j

dt r& =

r n r
+
q& j .
t j=1 q j

r&
r
= .
q& j q j

(8.2.4)

2
n
r
d r 2 r
+
q&

=
dt q j q jt =1 q jq

n r

+
q&

q j t
=1 q

dr
d r

=
dt q j q j dt

r&

qj

(8.2.5)

(8.2.4) (8.2.5) j ,
N

&

N
r&
m r&
+
q j =1
q j

j = d m r& r&
dt =1

(8.2.6)

T=

1 N
m r&2
2 =1

N
N
r&
r&
T
T
= m r& ,
= m r& .
q& j =1
q& j
q j =1
q j

151

j = d &T + T .
dt q j

(8.2.7)

q j

(8.2.3) q j , .
(8.2.3) q j , .

q j , (8.2.3) (8.2.7)
Qj

d T T
, j = 1, 2 ,..., n .

dt q& j q j

(8.2.8)

(8.2.8)

Lagrange , .
Q j U

= U(q j , t)

L =TU

T = T(q j , q& j , t) . L
q j q& j
L
T U
L
T
=

=
,
.
q j q j q j q& j q& j

(8.2.8)
d L L
= 0 , j = 1, 2 ,.., n .

dt q& j q j

(8.2.9)

L = TU

(8.2.10)

Lagrange
, ,
L = L(q j , q& j , t),j = 1, 2,..., n .

) Lagrange

Qj . Lagrange

d T T

dt q& j q j

Lagrange

Qj , j = 1, 2 ,3,...n .

(8.2.11)

(8.2.9) ,

U = U (q j ,q& j ,t) ,

152

d U U

dt q& j q j

Qj , j = 1, 2 ,3,...n .

(8.2.12)

Lagrange
d T T

dt q& j q j

d U U
,

dt q& j q j

j = 1, 2 ,3,...n .

L = T U ,

(8.2.13)

d L L

dt q& j q j

0 , j = 1, 2 ,3,...n .

(8.2.14)

L Lagrange

U ,
.
,
, Qj (8.2.12) ,
U
n

## U(q j ,q& j ,t) = (q j ,t)+ A k (q j ,t)q& k .

(8.2.15)

k=1

&
&
U = (x,y,z,t)+A1 (x,y,z,t)x+A
2 (x,y,z,t)y+A
3 (x,y,z,t)z& .

x
Qx =

dA1 =

A3
A 2
d U U dA1 A1
x& +
y& +
z& .
=

dt x& x
dt x
x
x
x

A1
A
A
A
dA1 A1
A
A
A
dx + 1 dy + 1 dz + 1 dt
=
x& + 1 y& + 1 z& + 1 .
x
y
z
t
t
x
y
z
t

Qx =

A3
A
A
A
A A
A 2

## + 1 x& + 1 y& + 1 z& + 1 1 x& +

y& +
z& .
x
x
y
z
t x
x
x

A = (A1 , A 2 , A3 ) ,

A3 A 2
A 2 A1
A1 A3
A = i

+ j

+k
z
x
y
z
y
x

Ax =

A 3 A 2
A1 A 3
A 2 A1

,A y =
,Az =
y
z
z
x
x
y

153

Qx
Qx =

= A y z& A z y& + 1 .
x
t

Q ,

Qy =

A 2

+ A z x& A x z& +
y
t

Qz =

A 3

+ A x y& A z x& +
z
t

Q = + ( A ) u +

A
,
t

(8.2.16)

## u = x& i + y& j + z& k .

A .
Lorentz

Q = q(E + u B) ,

(8.2.17)

q ,
. Lorentz
Q = q q( A ) u

A
t

(8.2.18)

Lorentz

U = q qA u .

(8.2.19)

) Rayleigh

r , = 1, 2,..., N,

r = r (q j , t) .

q j , j = 1, 2 ,3,..., n

Qj

F q

=1

## (ax& i + by& j + cz& k ) q

i+

y
q j

j+

z
q j

k .

n
r
r
r
r
dq j + dt r& = + q& j

q
t
t
j
j=1
j=1 q j

r&
r
= .
q& j q j

dr =

Qj

r&

F q&

=1

x
&

## (ax& i + by& j + cz& k ) q&

i+

&
y
&j
q

j+

z&
&j
q

k .

154

Qj =

1 N
(ax& 2 +by& 2 +cz& 2 ) .
2 q& j

R =

1 N
(ax& 2 +by& 2 +cz& 2 )
2

(8.2.20)

R
Qj

R
.
&j
q

(8.2.21)

R Rayleigh. R

: F dr
N

dW = F dr

=1

## F u dt = (ax& 2 +by& 2 +cz& 2 )dt = 2R dt .

=1

2R =

=1

dW
.
dt

Rayleigh ()
.
Lagrange N ,
Q j Qj ,
d T T

dt q& j q j

L = T U , Q j =

U
U = U(q j , t) ,
q j

d L L

dt q& j q j

Q j +Qj .

Qj , j = 1, 2 ,3,...n .

Lagrange

Rayleigh ,

d T T

dt q& j q j
d L L

dt q& j q j

R
&j
q

Qj

R
&j
q

, j = 1, 2 ,3,...n .

155

Lagrange

U = U(q j ,t) .

f = f(q j ,t) ,
.

## L(q j ,q& j ,t) = L(q j ,q& j ,t)+

df(q j ,t)
dt

(8.2.22)

d L L

dt q& j q j

0 , j = 1, 2 ,3,...n

(8.2.23)

L L .

df =

dq j +
j

df
f
f
dt = q q + t .

f
dt
t

&j

df(q j ,t)

=
dt
q j

d f

.
dt q j

f
f
q& j +
, j = 1, 2,3,...n .
t
j=1 q j

## L(q j ,q& j ,t) = L(q j ,q& j ,t) +

L L f
L L
df

=
+
=
+

q j q j q j dt
q& j q& j q j

L L d f
=
+
.
q j q j dt q j

d L L
, j = 1, 2 ,3,...n

dt q& j q j

d L L

dt q& j q j

d L f
+

dt q& j q j

q
j

df
.
q j dt

156

d L L

dt q& j q j

0 , j = 1, 2,3,...n .

(8.2.24)

Lagrange
L = L(q j ,q& j ,t) ,
L(q j ,q& j ,t) = L(q j ,q& j ,t)+

(8.2.25)

df(q j ,t)

(8.2.26)

dt

, (8.2.23) (8.2.24)
q j . Lagrange
(8.2.26),

df(q j ,t)
dt

, (8.2.24).
L L (8.2.23).
(8.2.22) Lagrange

Lagrange.
,
pj =

L L
df
f
.
=
+
= pj +

## q& j q& j q& j dt

q j

Lagrange
) Jacobi
8.3

q1 , q 2 , q3 . Lagrange .
T = T(q1 , q 2 , q3 , q& 1 , q& 2 , q& 3 ) U = U(q1 ,q 2 ,q3 ) . Lagrange

L = T U ,
L = L ( q1 , q 2 ,q3 ,q& 1 ,q& 2 ,q& 3 ) .

(8.3.1)

L
L
dL 3 L
&&
=
q& j +
qj .
q& j
dt j=1 q j

(8.3.2)

Lagrange (8.2.9)
d L L
, j = 1, 2,3 .

=
dt q& j q j

(8.3.2)

157

dL
dt

L
L
=
qj
+ &&

&j
q
j

q& j dt q&
j=1

L
d 3
q
.
&j
dt j=1 q& j

d 3 L
&j
q
L = 0
dt j=1 q& j

L
L =

q& j q&
j=1

(8.3.3)

Lagrange
(

L
= 0 ) Jacobi.
t

q1 , q 2 , q3

( ),
r = r (q1 ,q 2 ,q3 ) x = x(q1 , q 2 , q3 ) , y = y(q1 , q 2 , q3 ) , z = z(q1 , q 2 , q3 ) .
x
3

x
q& j

j=1 q j

x& =

(8.3.4)

& z
& .
y

T=

1
m(x& 2 +y& 2 +z& 2 )
2

(8.3.4)
T=

1
(q& 12 +bq& 22 +cq& 32 +2pq& 1q& 2 +2gq& 1q& 3 +2hq& 2 q& 3 ) .
2

(8.3.5)

(8.3.5) , b, c, p, h q1 , q 2 q3 .
T = T(q1 , q 2 , q3 , q& 1 , q& 2 , q& 3 ) .

(8.3.6)

L = T U , U = U(q1 ,q 2 ,q3 ) ,
L
T
.
=
&
q j q& j

(8.3.7)

(8.3.5)
q& 1 , q& 2 , q& 3
Euler,

158

T
q& j .
&

j=1 q j

2T =

(8.3.8)

## (8.3.7) (8.3.8) Jacobi

3

q&
j=1

q& j L = 2T (T U) = T+U = .

(8.3.9)

(8.3.9), ,
.

.
Lagrange

L = L(q j ,q& j ) ,

L
= 0
t

r = r (q j ) , , Jacobi(8.3.3),

. r = r (q j ,t) , ,

Jacobi .

f(x1 ,x 2 ,...,x n )

## f(x1 ,x 2 ,...,x n ) = f(x1 ,x 2 ,...,x n ) ,

f
f
f
x1 +
x 2 + ... +
x n = f(x1 ,x 2 ,...,x n ) .
x1
x 2
x n

x i = si ,i = 1, 2,3,...
.
f s1 f s 2
f s n
+
+ ...+
= 1f(x1 ,x 2 ,x 3 ,...x n ) .
s1 s 2
s n

f
f
f
x1 +
x 2 + ...+
x n = 1f(x1 ,x 2 ,x 3 ,...x n ) .
s1
s 2
s n

, =1. =1
f
f
f
x1 +
x 2 + ... +
x n = f(x1 ,x 2 ,...,x n ) .
x1
x 2
x n

) ( )

, ,
pj =

L
, j = 1, 2 ,3 .
q& j

(8.3.10)

159

Lagrange

qk ,

L
L
d L
d L
= 0 .
=

= 0 .
&
q k
q k
dt q k
dt q& k

pk =

L
= .
q& k

(8.3.11)

Lagrange ,
. (8.3.11)
q k .
n
,
f r (q1 ,q 2 ,...,q n ) = 0, r = 1, 2 ,..., k .

q& j ,
n n

T = jq& q& j

=1 j=1

j q j .
U = U(q1 ,q 2 ,...,q n ) .

q&
j=1

q& j L = T+U =

pk q k
pk =

L
= .
q& k

1. m Ox . x

Ox .

. Lagrange

L = TU =

1
m(x& 2 +y& 2 +z& 2 ) mgz .
2

L
L d dL
dL
d
& = 0 . mx
& = .
= 0 .
= mx& . (mx)
=

&
&
dt dx
dx
dt
x
x

2. .

q1 ,

,
.

160

x = r cos , y = r sin

Oz .

= q1

.
=
q1

x
= r sin = y,
q1

z
y
= 0.
= r cos = x
q1
q1

Lagrange
L = TU =

1
m(x& 2 +y& 2 +z& 2 ) U
2

U , ,
.

L=

1
1
m(r 2 sin 2 + r 2 cos 2 )& 2 U = mr 2 & 2 U ,
2
2
L

d L d
(mr 2 & ) .

=
dt & dt

mr 2 & =

.
.

m r 2 & = .

8.4

1.

P(r , m)

Ax+By+Cz = D

. .

.
r = xi + yj +

D Ax By
k.
C

r = xi + yj + zk , z =

D Ax By
.
C

T=

&
&
1
1
Ax+By
m(x& 2 +y& 2 +z& 2 ) = m x& 2 +y& 2 +

2
2
C

2
.

U = mgz , z = 0

. Lagrange
L = TU =

&
&
1 2 2 Ax+By
m x& +y& +

2
C

2
D Ax By
.
mg
C

161

Qj =

U
q j

q1 = x q 2 = y

.
mgA
mgB
, Q2 =
.
C
C

Q1 =

Lagrange
d L L

dt q& j q j

0 , j = 1, 2.

, , .

&&
x 1+

&&
y 1+

A2

AB
&&
y=
+
2
C C

mgA
C

B2 AB
mgB
&&
x=
.
+
2
C
C C

&&
x

A 2 +B2 +C2
C2

=g

A
A 2 +B2 +C2
B
, &&
y
=g .
2
C
C
C

2.
1
(1+2k)& 2 +2& & + & 2

2
1 2
U = n (1+k) 2 + 2

T=

n, k .
Lagrange
2
&& ) + n
(&&

1+k
( ) = 0.
k

, & = & =
. Lagrange (8.2.8)
Qj

t = 0 , = 0 t >0 .

d T T

dt q& j q j

Qj =

U
.
q j

q = , q = Q

Q .

162

2
&& = n (1 + k) ,
Q = (1 + 2k)&&
+

(1)

2
&& = n .
Q = &&
+

(1)

k,

(2)

(2)

1+k
k

2
&& ) + n
(&&

= s

1+k
( ) = 0.
k

(3)

n 2 (k+1)
= 2 (3) &&s+2 s = 0 s = A cos (t + 0 ) .
k

s = 0 , s& = 0 t = 0 .

A = 0 0 = 0, s = 0 t .

= t .

3. AB m

2 t

A m . t

=0

=0

F .

) x A O AOB

, .
2
) A g ,

F=

= 0 ( ) =

( )

mg
19 12 sin + 9 ( sin 2 cos 2 )
.
8

. C
& .

x c = x sin , y c = cos .

, T2

1
2

= m x& c2 +y& c2

T = T1 +T2 +T3 T1 =

1
mx& 2
2

T3
C .
T2 =

1
m x& cos &
2

1
2

1
2

1 m 2 & 2
.
2 3

## T = m x& 2 x& & cos + 2& 2 .

3

163

F rA = xi rA = xi .
rc

= x c i + yc j

rc

W = F rA

F mg .

= ( x cos ) i sin j .
+

B rc

Fx mg sin = Q x x+Q .

(8.2.8)
m

d
2x& & cos = Q x = F
dt

d
4 2&
& sin = Q
& cos +
&

x
mx
dt
3

= mg sin .

,
&& m&&
2mx
cos +m& 2 sin = F

(1)

4
m 2&&
m&&
x cos = mg sin .
3

(2) &&x = g

(2)

4 &&
= g ( cos sin ) .
3

(3)

, ,
2 & 2
= g ( sin + cos 1) .
3

(4)

## & 2 0 sin + cos 1 0 sin +

(1), &&x = g

+
0 .

4
2
4
4 4
2

(3) (4) .

164

4. OA

m 2 O .

m , O
k. . Lagrange
.

O . t OA

O OA = 0.
T1
T2 . T1 =

1
1
I112 + I2 22 , I1
2
2

OA O

1 = & , I2

1
I1 = m(2)2 .
3

O .

I2 =

O ,

I2 = 2 dm ,

= m/2 .
l sin dl = m
2

2 = & .

4 2
sin 2 .
3

T1 =

dm = dl , = l sin ,

11

2&2 1 & 2
4 2 sin 2 .
m4 + m
23
3

.
x O .
T2 =

1
1
1
2
&
mx& 2 + I3& 2 + I 4
2
2
2

I3 O
OA

I 4 O . I3 = mx& 2 , I4 = mx 2 sin2 .
T2 =

1
2
&
m x& 2 +x 2 & 2 +x 2 sin 2
.
2

165

T = T1 +T2 .

1
U = mg cos + mgx cos + k(x l 0 ) 2
2

x l 0 .

d L L

dt q& j q j

0,

q j . .
q1 = , q 2 = q3 = x .

4
2
2
& +x 2&&
& sin cos + m 2xx
& sin cos mg ( +x ) sin = 0 ,
&
m 2 &&

x 2
3
4
m 2
3

## ( sin2 + sin 2 ) + m ( 2xx sin2 +x 2 sin2 +x 2 sin 2 ) = 0 ,

&&

&&

&&

&&

&

m &&
x x& 2 + x& 2 sin2 + k ( x l 0 ) = 0.
&& = 0
& =
& = && = x& = &&x =

4 2

## +x 2 cos +g ( +x ) = 0 mx2 sin2 = k ( x l 0 ) .

3

5. P m M
.

Lagrange .
.

Oxyz Oz .
, ..,
Oz OP .
x 2 +y 2 +z 2 = 2 tan =

y
,
x

= t

166

y = 0 . x, y, z , x = cos sin ,

## y = sin sin z = cos , T1 =

1
m x& 2 +y& 2 +z& 2
2

x& = & cos cos sin sin , y& = & sin cos + cos sin , z& = & sin .
T1 =

1
m 2 & 2 + 2 2 sin 2 .
2

U = mgz .

T2 =

1 2
1
I I = M 2 . Lagrange
2
2
L = TU =

1
1
m 2 & 2 + 2 2 sin 2 + M 2 2 mg cos .
2
4

(7.7.9)

d L L

dt &

0.

m 2&&
m 2 2 sin cos mg sin = 0 .

6.

P Q m

O , P
Q . t = 0
P u 0 = 2g OP . .

P (r, )
T1 =

1
m &r 2 +r 2& 2 .
2

P
. Q r2 = zk , z
1
2

O . T2 = mz& 2 U 2 = mgz.

Lagrange

L = 12 m ( r

L1 = T1 U1

&

) = T2 U2 = 12 mz2 mgz.

+r 2 & 2 ,L 2

&

Lagrange
L = L1 +L 2 .

## (8.2.9 ) &&r r& 2 = 0 (1), r 2& = = u 0

r+z = . &&r+z&& = 0 , (3) &&r+g = 0
& =

u 0
r2

2g 2
r2

(4).

(2) &&
zg = 0

(3).

(2)

167

2r&&

2g3
r3

+ g = 0.

168